Elevated preoperative CEA is associated with worse survival in stage I-III rectal cancer patients - Tarantino, Ignazio; Warschkow, René (British journal of cancer, 2012)
Background:The objective of this investigation was to assess whether preoperative carcinoembryonic antigen (CEA) level is an independent predictor of overall survival in rectal cancer patients.Methods:All patients (n=504) undergoing a resection for stage I-III rectal cancer at the Kantonsspital St Gallen were included into a database between 1991 and 2008. The impact of preoperative CEA level on overall survival was assessed using risk-adjusted Cox proportional hazard regression models and propensity score methods.Results:In risk-adjusted Cox proportional hazard regression analyses, preoperative CEA level (hazard ratio (HR): 1.98, 95% confidence interval (CI): 1.36-2.90, P<0.001), distance from anal verge (<5 cm: HR: 1.93, 95% CI: 1.11-3.37; P=0.039), older age (HR: 1.07, 95% CI: 1.05-1.09; P<0.001), lower body mass index (HR: 0.94, 95% CI: 0.89-0.98; P=0.006), advanced tumour stage (stage II HR: 1.41, 95% CI: 0.85-2.32; stage III HR: 2.08, 95% CI: 1.31-3.31; P=0.004), R 1 resection (HR: 5.65, 95% CI: 1.59-20.1; P=0.005) and chronic kidney disease (HR: 2.28, 95% CI: 1.03-5.04; P=0.049) were all predictors for poor overall survival.Conclusion:This is one of the first investigations based on a large cohort of exclusively rectal cancer patients demonstrating that preoperative CEA level is a strong predictor of decreased overall survival. Preoperative CEA should be used as a prognostic factor in the preoperative assessment of rectal cancer patients.
Gesehen am 12.07.2018
Corrected online 03 July 2012, published online 26 June 2012